Evaluation of various silo sorghum hybrids from the energetic aspect - Jóvér, János; Ábrahám, Éva; Blaskó, Lajos (Acta Agraria Debreceniensis, 2013)
The sweet sorghum is a perspective plant of bioenergy, which can be the foundation of Hungarian bioethanol production in the future. By the examination six sweet sorghum hybrids have been examinated by the viewpoint of sugar aggregation and bioethanol production capacity. The founda tion of the surve y was three growing se ason (201 0, 2011, 2012 ). The ex per ime nt w as on the production sites of U niversity of Debrecen CAAES RISF Karcag Research Institute. The production site of the sweet sorghum have been sampled by samples of 1 m2 by hybrids within the period of august 15 and november 15. The sugar content of the samples have been measured by refractometer which was the base in the determination of ethanol production capacity. As a continuation of the evaluation of energetic viewpoint the Higher Heating Value (HHV) have been measured from the bagasse of sweet sorghums. According to the results it can be stated that int he case of sugarcontent and the dinamics of the sugar aggregation can show several differences, while HHV of sorghum bagasse is within 16 200 and 16 900 J g-1.